Changes in oxidative stress from tracheal aspirates sampled during chest physical therapy in hospitalized intubated infant patients with pneumonia and secretion retention - Leelarungrayub J; Borisuthibandit T; Yankai A; Boontha K (Dove Medical Press, 2016)
Jirakrit Leelarungrayub,1 Thirasak Borisuthibandit,2 Araya Yankai,1 Kritsana Boontha1 1Department of Physical Therapy, Faculty of Associated Medical Sciences, 2Department of Pediatric, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand Objective: This study aimed to show the changes in oxidative stress and clinical condition from either chest physical therapy (CPT) or CPT with aerosol treatment in infant patients with pneumonia.Methods: From 52 intubated patients, three groups were composed: groups A, B, and C comprising 21 patients aged 5.3±0.6 months (CPT program), 20 patients aged 5.6±0.7 months (aerosol treatment before CPT program), and eleven patients aged 5.0±0.35 months (control), respectively. CPT was composed of manual percussion and vibration before suction in a specific position for draining secretion and re-expanding collapsed lungs. Groups A and B received three sessions of treatment three times daily for 6 days, when tracheal aspirates were collected for evaluating oxidative stress markers for the thiol group: vitamin E, thiobarbituric acid reactive substances-malondialdehyde, and hyarulonan. Furthermore, lung injury score and oxygenation index (PvO2/FiO2 ratio) were recorded daily.Results: All parameters in group C did not change statistically during study. The thiol group increased significantly in group A after day 4, and increased significantly on days 3 and 6 when compared to day 1 in group B. Vitamin E levels increased significantly on days 3, 5, and 6 in group A, and days 3, 4, and 6 in group B, when compared to day 1. Whereas, the thiobarbituric acid reactive substances-malondialdehyde adduct showed a significant reduction after day 4 in groups A and B, when compared to day 1. Hyarulonan levels showed a significant reduction after day 3 in group A and on day 2 in group B. In addition, lung injury score decreased slightly and nonsignificantly in groups A and B, whereas the oxygenation index increased significantly after day 4 in group A and on day 6 in group B.Conclusion: These preliminary results suggest that CPT with or without aerosol treatment possibly reduces oxidative stress and enhances oxygenation status in infant patients. Keywords: chest physical therapy, oxidative stress, lung injury, oxygenation index, pneumonia